Peran Pesantren dalam Pemberdayaan Perempuan: : Kajian Perspektif Gender dalam Pendidikan Islam - Nurhidayati, Vivi (TSAQAFATUNA : Jurnal Ilmu Pendidikan Islam, 2025)
Pesantren, as Islamic educational institutions, play a significant role in the empowerment of women, particularly in promoting gender equality through education based on religious values. However, there is still a prevailing perception that pesantren tend to uphold patriarchal values that limit women's mobility and participation in various aspects of life. The inconsistency between the principles of justice in Islam and the social practices in some pesantren raises questions about the extent to which these institutions can serve as inclusive and progressive spaces for promoting women's empowerment. This article aims to examine the role of pesantren in empowering women using a literature review approach. The findings indicate that pesantren are capable of transforming into agents of change that support gender-equitable development through inclusive curricula, the strengthening of female leadership roles, and the development of economic skills. These findings underscore the need for internal reform within pesantren so that Islamic values not only provide spiritual education but also promote social justice for women.